Advanced robotics and additive manufacturing of composites: towards a new era in Industry 4.0 - Parmar, Hetal; Khan, Tayyab; Tucci, Fausto; Umer, Rehan; Carlone, Pierpaolo (Materials and manufacturing processes, 2022)
In recent years, new revolutionary paradigms generally indicated using the term Industry 4.0, have been conceived and are progressively applied in several manufacturing systems to achieve a smarter, more effective, and sustainable production. This article aims to depict the present and future scenarios related to the application of Industry 4.0 concepts to polymer composites manufacturing. To provide a view on future potential, and open new research frontiers, the article attempts to address through elaborate discussions two major questions: What is the future of fiber-reinforced polymer composites manufacturing in the Industry 4.0 context? What are the recent and potential developments in robotic and additive manufacturing of advanced fiber-reinforced composites? The article, in addition, connects new avenues in additive manufacturing, for instance, incorporating topology optimization, design opportunities, recent industrial developments in machines and patent disclosures, and defect detection/mitigation during manufacture. Similarly, recent developments concerning robotic Automated Fiber/Tape Placement have been provided, discussing state-of-the-art research trends and future opportunities.